Abuse of circumstances in agreements among businesses and micro, small and medium enterprises - Soetopo, Maria G.S. (Jurnal Indovisi, 2025)
The Micro, Small, and Medium Enterprises (MSMEs) sector plays a vital role in the national economic development. In order to support MSMEs, partnership agreements among businesses and MSMEs are optimized through contract enforcement by the government. However, Indonesian Civil Code has not included provisions on misbruik van omstandigheden which often place MSMEs in a weaker position. This study aims to outline and analyze legal issues related to the concept of misbruik van omstandigheden in partnership agreements, using a normative legal research method with a conceptual, statutory, and comparative approaches in forming the arguments. Findings indicate that MSMEs’ weakened position in partnership agreements is due to a lack of implementing regulations on misbruik van omstandigheden based on the Indonesian Civil Code regarding agreement termination, both in legal practice and in judges’ decision-making mechanism within court proceedings in Indonesia.